2022
DOI: 10.1111/jopr.13481
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Cycling Effect on Locator System Retention and Metal Surface Roughness

Abstract: Purpose To estimate the effects of the thermal cycling (TC) process on the metal surfaces of Locators, as well as retention loss, and the correlation between them. Materials and methods Twenty‐five new Locator R‐Tx were included in the study. Four areas were marked on each Locators’ patrix metal surface and scanned using a confocal scanner (μsurf explorer; NanoFocus). Three surface roughness parameters were measured in the scans: Sa (average distance of peaks from the central plain of the area), Vmp (volume of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(106 reference statements)
0
1
1
Order By: Relevance
“…The thermal effect may explain these results, as it can cause changes in the retentive insert size within the matrix housing and providing increased retention. In contrast, a study reported the retentive force of the blue-coded retentive insert in the LOCATOR R-Tx attachment decreased after thermocycling, and also reported a greater retentive force of retentive insert than the present data 24) . These findings might be explained by differences in the cycle of thermocycling testing and dislodgement speed.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The thermal effect may explain these results, as it can cause changes in the retentive insert size within the matrix housing and providing increased retention. In contrast, a study reported the retentive force of the blue-coded retentive insert in the LOCATOR R-Tx attachment decreased after thermocycling, and also reported a greater retentive force of retentive insert than the present data 24) . These findings might be explained by differences in the cycle of thermocycling testing and dislodgement speed.…”
Section: Discussioncontrasting
confidence: 99%
“…This material wear is caused by several etiological factors 19) , including material type 20) , implant position 13,21) , the frequency of denture insertion/removals 10,11,17,22) , interimplant angulation 22) , brushing habits 23) , and cyclic loading 14) . Moreover, thermal change might influence overdenture retention [24][25][26] . Denture attachments undergo multiple thermal fluctuations throughout the day during activities such as eating, drinking hot or cold liquids, and even breathing.…”
Section: Introductionmentioning
confidence: 99%